2020
DOI: 10.1186/s13045-019-0838-y
|View full text |Cite
|
Sign up to set email alerts
|

Axicabtagene ciloleucel CD19 CAR-T cell therapy results in high rates of systemic and neurologic remissions in ten patients with refractory large B cell lymphoma including two with HIV and viral hepatitis

Abstract: Axicabtagene ciloleucel (Axi-cel) is a CD-19 Chimeric Antigen Receptor T cell therapy approved for the treatment of relapsed/refractory diffuse large B cell lymphoma. We treated ten patients with DLBCL post-FDA approval in an inner-city tertiary center in the Bronx. Eight patients (80%) had received ≥ 3 lines of therapy, six patients had received prior radiation, and seven had recurrent disease after prior autologous hematopoietic stem cell transplant (AHCT). Our cohort included one patient with HIV, two patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
177
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(186 citation statements)
references
References 10 publications
9
177
0
Order By: Relevance
“…Recently, chimeric antigen receptor T cells (CAR-T cells) have emerged as a promising therapy for treating B cellderived malignancy [1,2]. Two CAR-T cell products have been approved by the FDA to treat B-cell leukemia and lymphoma [3][4][5][6]. CAR-T cells against tumor-specific antigens (TSA), including mesothelin (MSLN) and glypican 3 (GPC3) are being actively tested for treating nonsmall-cell lung cancer (NSCLC) and hepatocellular carcinoma, respectively [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chimeric antigen receptor T cells (CAR-T cells) have emerged as a promising therapy for treating B cellderived malignancy [1,2]. Two CAR-T cell products have been approved by the FDA to treat B-cell leukemia and lymphoma [3][4][5][6]. CAR-T cells against tumor-specific antigens (TSA), including mesothelin (MSLN) and glypican 3 (GPC3) are being actively tested for treating nonsmall-cell lung cancer (NSCLC) and hepatocellular carcinoma, respectively [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The European Society for Blood and Marrow Transplantation (EBMT) and the Joint Accreditation Committee of ISCT and EBMT (JACIE) practice recommendations have suggested that pharmaceutical companies could manufacture CAR T cells for HIV-positive patients if the viral load was undetectable after anti-retroviral treatment [54]. The published clinical experience is limited to three patients with HIV successfully treated with CAR T cells without additional toxicity [55,56].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…To develop the lung cancer cell line xenograft models, 5×10 5 H460GL cells in 200 μl of PBS were injected subcutaneously into the right anks of NOD-SCID-IL2Rg-/-(NSI) mice aged 6-8 weeks. Ten days after tumor cell transplantation, 5×10 6 CAR T cells were injected through the tail vein of mice. Tumors were measured at indicated days with a caliper to determine the subcutaneous growth rate.…”
Section: Xenograft Models and In Vivo Assessmentmentioning
confidence: 99%
“…Then, 10, 15, 20 or 24 days after tumor transplantation, mice were infused with CAR T cell or control T cells. In total, 5×10 6 CAR T cells were injected one time into each mouse. Tumors were measured with a caliper, and tumor volume was calculated using the following equation: (length×width×width)/2.…”
Section: Xenograft Models and In Vivo Assessmentmentioning
confidence: 99%
See 1 more Smart Citation